2021
DOI: 10.1680/jgeen.20.00219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the installation process on monopile lateral response

Abstract: Most offshore wind turbines (OWTs) are supported by large-diameter monopiles, installed by impact driving. OWTs are dynamically sensitive structures, with a narrow design range for the eigenfrequency. Fatigue and serviceability limit states can be critical in design, so the foundation stiffness plays an important role. The pile installation process results in changes to the soil state, investigated here through large-deformation numerical analyses using the coupled Eulerian–Lagrangian approach with a hypoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Accounting for the effects of the coupled pore fluid-stress response during the installation leads to a lateral response comparable to that of a WIP pile. Overall though the influence of the installation process on the monotonic pile response is less significant for the high ratio of pile diameter and wall thickness D/t considered here than in cases with lower D/t (for simulations with lower ratio D/t see (Staubach et al, 2020b;Staubach et al, 2021a;Bienen et al, 2021;Le et al, 2021;Fan et al, 2021a)). Therefore, the assumption of WIP conditions for piles with a larger D/t ratio, such as for instance applied by recent numerical studies reported e.g.…”
Section: Numerical Model For the Lateral Loadingmentioning
confidence: 83%
See 1 more Smart Citation
“…Accounting for the effects of the coupled pore fluid-stress response during the installation leads to a lateral response comparable to that of a WIP pile. Overall though the influence of the installation process on the monotonic pile response is less significant for the high ratio of pile diameter and wall thickness D/t considered here than in cases with lower D/t (for simulations with lower ratio D/t see (Staubach et al, 2020b;Staubach et al, 2021a;Bienen et al, 2021;Le et al, 2021;Fan et al, 2021a)). Therefore, the assumption of WIP conditions for piles with a larger D/t ratio, such as for instance applied by recent numerical studies reported e.g.…”
Section: Numerical Model For the Lateral Loadingmentioning
confidence: 83%
“…A numerical method able to model large-deformations is required for the analysis of pile installation processes. Simulations using the Coupled Eulerian-Lagrangian (CEL) method (Qiu et al, 2011;Henke, 2014;Hamann et al, 2015;Fan et al, 2021c;Bienen et al, 2021), the (Multi-Material) Arbitrary Lagrangian Eulerian method (Liyanapathirana, 2009;Tolooiyan and Gavin, 2011;Dijkstra et al, 2011;Aubram et al, 2015;Yang et al, 2020), the Material Point Method (Phuong et al, 2014;Hamad, 2016;Ceccato and Simonini, 2017;Giridharan et al, 2020;Martinelli and Galavi, 2021), the Particle FEM (Hauser and Schweiger, 2021;Monforte et al, 2021;Zhang et al, 2021), the Discrete Element Method (Ciantia et al, 2016;Li et al, 2019) and the Smoothed Particle Hydrodynamics method (Cyril et al, 2019) are reported in the literature. A discussion of the different methods as well as of their advantages and disadvantages in applications to geotechnical boundary value problems is out of the scope of this work.…”
Section: Numerical Simulation Of the Installation Processmentioning
confidence: 99%